2016
DOI: 10.1016/s0140-6736(15)00803-x
|View full text |Cite
|
Sign up to set email alerts
|

Liraglutide safety and efficacy in patients with non-alcoholic steatohepatitis (LEAN): a multicentre, double-blind, randomised, placebo-controlled phase 2 study

Abstract: Wellcome Trust, National Institute of Health Research, and Novo Nordisk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
1,351
6
55

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,627 publications
(1,450 citation statements)
references
References 31 publications
38
1,351
6
55
Order By: Relevance
“…GLP‐1R agonists increase glucose‐induced insulin secretion, decrease glucagon secretion and hepatic glucose output, and promote satiety leading to weigh loss 22. A recent multicenter, double‐blind, randomized, placebo‐controlled phase 2 study assessed the efficacy of liraglutide 1.8 mg daily for 48 weeks in patients with NASH (the LEAN study) 23. NASH resolution was noted in a significantly higher proportion of patients who received liraglutide (39%) than those who were in the placebo arm (9%, P = 0.019).…”
Section: Nafld/nash‐specific Therapiesmentioning
confidence: 99%
“…GLP‐1R agonists increase glucose‐induced insulin secretion, decrease glucagon secretion and hepatic glucose output, and promote satiety leading to weigh loss 22. A recent multicenter, double‐blind, randomized, placebo‐controlled phase 2 study assessed the efficacy of liraglutide 1.8 mg daily for 48 weeks in patients with NASH (the LEAN study) 23. NASH resolution was noted in a significantly higher proportion of patients who received liraglutide (39%) than those who were in the placebo arm (9%, P = 0.019).…”
Section: Nafld/nash‐specific Therapiesmentioning
confidence: 99%
“…Although there is not good evidence of GLP-1 receptor expression in the human liver, the safety and efficacy of liraglutide at a dose of 1.8 mg/day was recently tested in a small randomised clinical trial in patients with biopsy-confirmed NASH [58], as specified in the section below.…”
Section: Secreted Hepatokines and The Role Of Incretins And Glucagonmentioning
confidence: 99%
“…Considering that insulin resistance is the hallmark of NAFLD, drugs acting on glucose metabolism have long been considered for NAFLD treatment [35,58,[72][73][74][75][76][77][78][79][80]. Insulin sensitizers have been tested in several clinical trials of different duration.…”
Section: Drug Treatment Of Nafld With a Defined Impact On Glucose Metmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 Several anti-diabetic therapies have been investigated in the treatment of NASH with varying success, including metformin, [10][11][12] rosiglitazone, 13,14 pioglitazone, [15][16][17] and liraglutide. 18 Sitagliptin is an oral antihyperglycemic agent that competitively inhibits the enzyme dipeptidyl peptidase 4 (DPP-4), which inactivates the hormones glucagon-like peptide-1 (GLP-1) and glucose-dependent insulinotropic polypeptide (GIP) released in response to meals. By blocking GLP-1 and GIP breakdown, sitagliptin increases insulin secretion and suppresses glucagon release in the pancreas, 19 which lowers blood glucose levels and improves hemoglobin A1c (HbA1c).…”
Section: Introductionmentioning
confidence: 99%